The Role of TikTok Content Translation in the Development of Social Media Language among Students in Primary Education - Rahma Ilyas; Wina Dwi Puspitasari; Nanda Yuliana (Journal of Innovation and Research in Primary Education, 2026)
The development of social media, especially TikTok, has created a new space for primary education students to interact and develop language practices, including through exposure to foreign-language content presented with translations. This situation raises the question of how the translation of TikTok content plays a role in the development of social media language among primary school students. This study aims to analyze the role of English–Indonesian TikTok content translation in understanding messages, user responses, and its contribution to the formation of vocabulary and language styles used by students. The research employs a qualitative method with a case study approach. Data were obtained from several English-language TikTok videos with Indonesian translations, translation texts, and user comments reflecting their responses and interpretations of the content. Data were collected through documentation and analyzed using content analysis and thematic analysis to identify patterns of meaning and emerging language dynamics. The results indicate that accurate and contextual translation helps students understand humor, motivation, and emotional expression, while also fostering the emergence of new vocabulary and expressions in Indonesian that are widely adopted in digital spaces. Translation also plays a role in shaping a relaxed and creative language style that aligns with students' daily lives. These findings suggest that TikTok content translation not only bridges languages but also has practical implications for the development of language literacy and digital literacy at the primary education level.